Effet de l’uranium sur le comportement physiologique et chimique de la féverole (Vicia faba L. minor) - Daines, Mohamed El Amine (My University, 2018)
Uranium constitute a major constraint to the environment and the sustainable development approach by degrading the ecosystem. The objective of the present work is to study the effect of uranyl nitrates on some biometric, physiological and chemical parameters of a species commonly cultivated in Algeria, the faba bean Vicia faba L minor, variety Sidi Aich. Seeding takes place in a semi-automated greenhouse and in 8 kg plastic pots filled with a substrate that contains 2/3 clay, 1/3 sand and potting soil. The bottom of each pot has been filled with gravel to ensure good drainage, the irrigation is made to the reserve easily usable. 110 day old plants subjected to increasing doses of uranyl nitate 20; 40 and 60 ppm then were dug up for physiological, chemical analyzes in the laboratory. The results show significant accumulation of uranium in the aerial, underground and pods with the largest cumulative amount remaining in the roots of faba beans at doses of 40 and 60 ppm. There is also an increase in root weight, stem length, root surface and thickness of sap-conducting vessels against a decrease in chlorophyll "a" and the relative water content in the plant.
Keywords: uranium; physiologie; féverole; accumulation; phytoremédiation; physiology; faba bean; accumulation; phytoremediation